Genetic Characterization of a blaVIM–24-Carrying IncP-7β Plasmid p1160-VIM and a blaVIM–4-Harboring Integrative and Conjugative Element Tn6413 From Clinical Pseudomonas aeruginosa - Zeng, Lijun; Zhan, Zhe; Hu, Lingfei; Jiang, Xiaoyuan; Zhang, Yanjun; Feng, Jiao; Gao, Bo; Zhao, Yuee; Yang, Wenhui; Yang, Huiying; Yin, Zhe; Zhou, Dongsheng (Frontiers in Microbiology, 2019)
This study presents three novel integrons In1394, In1395, and In1443, three novel unit transposons Tn6392, Tn6393, and Tn6403, one novel conjugative element (ICE) Tn6413, and the first sequenced IncP-7 resistance plasmid p1160-VIM from clinical Pseudomonas aeruginosa. Detailed sequence comparison of p1160-VIM (carrying Tn6392 and Tn6393) and Tn6413 (carrying Tn6403) with related elements were performed. Tn6392, Tn6393, and Tn6403 were generated from integration of In1394 (carrying blaVIM–24), In1395 and In1443 (carrying blaVIM–4) into prototype Tn3-family unit transposons Tn5563, Tn1403, and Tn6346, respectively. To the best of our knowledge, this is the first report of a blaVIM–24-carrying P. aeruginosa isolate.